(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article investigates the use and classification of the -ing form in English, a versatile morphological structure that functions predominantly as a gerund, present participle, and deverbal noun. Through a descriptive-analytical approach, various grammatical roles and syntactic environments of the -ing form are examined. The study highlights the semantic and functional distinctions among the categories and explores their frequency and distribution in contemporary English. Findings suggest that the -ing form serves critical roles in verbal and nominal constructions, contributing to the language’s expressive flexibility. The article concludes with implications for linguistic theory and English language teaching